2022
DOI: 10.1039/d2ra01919a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design and synthesis of a novel long-chain 4′′-alkyl ether derivative of EGCG as potent EGFR inhibitor: in vitro and in silico studies

Abstract: Among the synthesized 4′′-alkyl EGCG derivatives, 4′′-C14 EGCG inhibited EGF stimulated phosphorylation of EGFR and its downstream signaling pathways, ERK and Akt. 4′′-C14 EGCG showed significantly improved stability than EGCG and induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 91 publications
0
25
3
Order By: Relevance
“…We examined the expression level of cleaved caspase-3. The intrinsic and extrinsic pathways are essential in activating the caspase cascade, a common characteristic biological feature during apoptosis. , We selected the obtained IC 50 values of C1 (15.01 μM), C2 (24.05 μM), GC1 (7.50 μM), and GC2 (10.17 μM) for the Western blot experiments. After exposing the HeLa cells to synthesized compounds for 24 h, Western blot results showed the cleavage of caspase-3 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We examined the expression level of cleaved caspase-3. The intrinsic and extrinsic pathways are essential in activating the caspase cascade, a common characteristic biological feature during apoptosis. , We selected the obtained IC 50 values of C1 (15.01 μM), C2 (24.05 μM), GC1 (7.50 μM), and GC2 (10.17 μM) for the Western blot experiments. After exposing the HeLa cells to synthesized compounds for 24 h, Western blot results showed the cleavage of caspase-3 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…54 Therefore, western blot experiments were carried out to explore the effects of ruthenium-based complexes on the expression of cleaved caspase-3. 55 The results obtained from immunoblot analysis strongly suggested that all three complexes remarkably upregulate the expression of cleaved caspase-3. However, compared to the control, complex 2 increases the cleaved caspase-3 expression most, followed by complex 1 and complex 3 .…”
Section: In Vitro Cell Viability Assaymentioning
confidence: 94%
“…In silico methods are very useful in modeling epidemiology‐based data, identifying targeted therapies for novel drug design, repurposing drugs, predicting vaccine epitopes, and formulating diagnostic models for COVID‐19 35,36 . In addition, computational screening, such as molecular docking and MD simulations, can identify the significant roles of phytochemicals as adjuvants and assist in the selection of candidates for in vivo experiments 37 …”
Section: Introductionmentioning
confidence: 99%
“…35,36 In addition, computational screening, such as molecular docking and MD simulations, can identify the significant roles of phytochemicals as adjuvants and assist in the selection of candidates for in vivo experiments. 37 This computational study was carried out to investigate the interactions of Omicron SGp RBD from variants BA.1, BA.…”
mentioning
confidence: 99%